2017
DOI: 10.1016/j.jalgebra.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Words and characters in finite p-groups

Abstract: Given a group word w in k variables, a finite group G and g ∈ G, we consider the number N w,G (g) of k-tuples g 1 , . . . , g k of elements of G such that w(g 1 , . . . , g k ) = g. In this work we study the functions N w,G for the class of nilpotent groups of nilpotency class 2. We show that, for the groups in this class, N w,G (1) ≥ |G| k−1 , an inequality that can be improved to N w,G (1) ≥ |G| k /|G w | (G w is the set of values taken by w on G) if G has odd order. This last result is explained by the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Levy has shown that when G has nilpotent class 2, then for any word w we have µ G,w (1) ≥ 1 |G| [Lev11]; showing that Amit's Conjecture holds for class 2 groups. Iñiguez and Sangroniz have shown the stronger condition that for free p-groups of nilpotency class 2 and exponent 2, it is true that µ G,w (g) ≥ 1 |G| [InS17]. Klyachko and Mkrtchyan [KM14] considered first-order formula in any finite group, which implies µ G,w (1) ≥ 1 |G| when w has only 2 variables.…”
Section: Lemma 6 [Coc]mentioning
confidence: 99%
“…Levy has shown that when G has nilpotent class 2, then for any word w we have µ G,w (1) ≥ 1 |G| [Lev11]; showing that Amit's Conjecture holds for class 2 groups. Iñiguez and Sangroniz have shown the stronger condition that for free p-groups of nilpotency class 2 and exponent 2, it is true that µ G,w (g) ≥ 1 |G| [InS17]. Klyachko and Mkrtchyan [KM14] considered first-order formula in any finite group, which implies µ G,w (1) ≥ 1 |G| when w has only 2 variables.…”
Section: Lemma 6 [Coc]mentioning
confidence: 99%
“…is unique for any χ ∈ Irr(G). Much about the functions N w,G , or rather P w,G = N w,G /|G| k , has been done, particularly for the commutator word w = [x, y] and for the case G is a p-group for some prime p; see [1,4,9,12,13,22] and also [2,3,7,8,10,18]. In addition, Nikolov and Segal [20] gave a characterization of finite nilpotent groups and of finite solvable groups based on the function P w,G : a finite group is nilpotent if and only if the values of P w,G (g) are bounded away from zero as g ranges over G w and w ranges over all group words; and a finite group is solvable if and only if the probabilities P w,G (1) are bounded away from zero as w ranges over all group words.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nikolov and Segal [20] gave a characterization of finite nilpotent groups and of finite solvable groups based on the function P w,G : a finite group is nilpotent if and only if the values of P w,G (g) are bounded away from zero as g ranges over G w and w ranges over all group words; and a finite group is solvable if and only if the probabilities P w,G (1) are bounded away from zero as w ranges over all group words. Iñiguez and Sangroniz [13] proved that for any finite group G of nilpotency class 2 and any word w, the function N w is a generalized character of G, that is, a Z-linear combination of irreducible characters. What is more, if G is a finite p-group of nilpotency class 2 with p odd and w any word, then N w is a character of G. In general, for p = 2, the function N w is not a character; one can easily check for N x 2 ,Q8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations